2021
DOI: 10.26877/eternal.v12i2.9211
|View full text |Cite
|
Sign up to set email alerts
|

EFL teachers’ perception towards online classroom interaction during covid-19 pandemic

Abstract: The spread of Covid-19 is affecting education systems around the world and transform the learning from face-to-face to online learning. Interaction is important pattern to share knowledge between teachers and students. Previous research has said that interaction could also encourage students to master the subject matter. This study aims to describe the EFL teachers’ perception towards classroom interaction during Covid-19 pandemic especially on how the interaction between teacher-student, student-teacher, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In terms of participation and classroom interaction, the teacher educators seemed to be dissatisfied with the performance of teacher candidates regardless of their types in this regard. Studies dealing with the level of interaction within online settings revealed that compared to face-to-face, classroom interaction decreases in online instruction (Kusuma et al, 2021;Wut & Xu, 2021;Yazgan, 2022). According to Yazgan (2022), not having enough opportunities to communicate, not being able to participate in social activities, and the exhaustion of online interaction created a gap between students, and this new form of interaction had a negative impact on learning.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of participation and classroom interaction, the teacher educators seemed to be dissatisfied with the performance of teacher candidates regardless of their types in this regard. Studies dealing with the level of interaction within online settings revealed that compared to face-to-face, classroom interaction decreases in online instruction (Kusuma et al, 2021;Wut & Xu, 2021;Yazgan, 2022). According to Yazgan (2022), not having enough opportunities to communicate, not being able to participate in social activities, and the exhaustion of online interaction created a gap between students, and this new form of interaction had a negative impact on learning.…”
Section: Discussionmentioning
confidence: 99%
“…1 above, it can be seen that video conferencing applications like Zoom, Google Meet, Skype, Cisco WebEx, Discord, and Microsoft Team are used for synchronous online learning in English language classrooms in Indonesian schools and universities. Principally, those video conferencing applications have similar function, facilitating a two-way communication between teachers and their students, in the same time, engaging students with their classmates in a real-time basis (Atmojo & Nugroho, 2020;Kusuma, et al, 2021;Lie & Prijambodo, 2021;Putri & Sari, 2022). Zoom, Google Meet, Skype, Cisco WebEx, Discord, and Microsoft Team applications provide teachers with various supporting features such as screen sharing where teachers could display the materials on the screen to aid understanding, mics feature where teacher and students can talk as well as respond to each other, chat box where students can respond in a form of writing text and upload files.…”
Section: Synchronous Online Learning In English Language Classrooms I...mentioning
confidence: 99%